Blockchain-based mass customization framework using optimized production management for industry 4.0 applications - Yetis, Hasan; Karakose, Mehmet; Baygin, Nursena (Elsevier - Division Reed Elsevier India Pvt Ltd, 2022)
Customers want to experience unique products that suit their individual preferences. Therefore, companies are looking for ways to produce personalized products by moving away from traditional production models. Technologies such as blockchain, IoT, and cyber-physical systems have an important role in adopting the personal custom production model. In this study, a reliable and optimized mass customization framework is proposed. The framework has three main contributions. First, the use of Blockchain provides advantages in terms of data persistence, traceability, transparency, and reliability. Second, the production process is optimized by using artificial intelligence methods. A decision support mechanism is proposed for customers who will place orders. As a combination of the contributions, the proposed mass customization framework covers the processes from ordering to production. In addition to contributions such as facilitated customization and reliable data, energy saving in production is increased with the proposed framework. Simulation results show that energy savings between 10 and 47% are achieved.(c) 2022 Karabuk University. Publishing services by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: Industry 4; 0; Mass customization; Energy efficiency; Blockchain